Legislations on Juvenile Delinquency - Dr. Amritpal Kaur, Tripti Sada Singh, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The unusual status of children through Articles 15(3), 21A, 24, 39(e), 39(f) and 45 has been acknowledge by the Indian Constitution. The above articles grant special provision for the children by the states to protect their rights and liberties along with protecting them from every kind of abuse and injustice. The above articles preserve the rights of the children for their upliftment and development. The present paper aims to discuss the legislation with regard to juvenile justice system and the history of legislations that came into existence right from its inception. One after another how one legislation repealed the earlier one making a list of acts that covered the juvenile justice system. The changes which were adopted with time in these acts have been discussed in this paper. Critical analysis of the acts as to what made it insufficient to survive. Besides this, the loopholes in the acts which made way for repealing of the acts. What were the circumstances for passing the Juvenile Justice (Care and Protection of Children) Act, 2015? And at the end, the existing law on juvenile delinquency and juvenile justice system along with the conclusion has been discussed at greater length. The following research paper intents to study the history of legislations on juvenile delinquency.